Gambaran Tingkat Pengetahuan Tentang Anemia pada Remaja Putri di Pesantren Dar Maryam Aceh Besar - Hafni Zahara; Maula Habna (Universitas Muhammadiyah Manado, 2025)
Anemia is a global public health problem that has a serious impact, especially on young children, adolescent girls, pregnant women, and postpartum women. This condition is characterized by lower than normal hemoglobin (Hb) levels in the blood, thus interfering with the function of body tissues due to lack of oxygen. The impact includes a decrease in learning concentration, productivity, and endurance. This study aims to determine the level of knowledge of adolescent girls about anemia at the Dar Maryam Aceh Besar Islamic Boarding School. The study used a descriptive approach with a purposive sampling technique, involving 38 respondents. Data was collected through interviews using questionnaires. The results showed that 6 people (16%) had very good knowledge, 24 people (63%) had good knowledge, and 8 people (21%) had poor knowledge. Good knowledge plays an important role in increasing adolescents' awareness of nutritious food consumption patterns and healthy living behaviors. This study recommends increasing nutrition education, regular consumption of blood-boosting tablets, and periodic health check-ups with the assistance of medical personnel. This effort is expected to be able to increase knowledge and prevent anemia in adolescent girls in a sustainable manner.